Assessment of Library Information Resources Utilization by Students of College of Education Akwanga, Nasarawa State – Nigeria - Faga, Asom; Thomas, Paul Ogor; Lushima , Dzenda (Communicate: Journal of Library and Information Science, 2024)
The study assessed library information resources utilization by students of College of Education Akwanga, Nasarawa State – Nigeria. Three specific objectives with corresponding research questions guided the study. The study adopted a descriptive research design. A sample of 352 final year-students of the College of Education Akwanga, Nasarawa State was used as the population of the study. The instrument for data collection for the study was a self-developed structured questionnaire Data collected was analyzed using Frequency Counts, Percentages, Means and Standard Deviation. Findings of the study revealed that students utilize a range of information resources such as textbooks, journals, magazines/newspapers, indexes, abstracts, reference materials, maps, encyclopedia, dictionary, projects, gazettes, and atlases. In addition, the research indicated a high extent of information resource utilization among students of College of Education Akwanga. However, challenges were identified, including poor indexing of information resources, insufficient relevant resources in the library, and the outdated nature of available information resources which pose obstacles to the effective utilization of information resources by students. The recommendations stemming from these findings include the need for College of Education Akwanga Library to organize user education or workshops at the start of each semester, targeting all categories of students among other recommendations.